The Literacy Processes of Text Messages on Social Networks for the Teaching of ele - Waked-Hernández, Myriam (Rastros Rostros, 2016)
Introduction: This article presents the results of the research study titled “Implementation of the c1 level of the Common European Framework of Reference for Languages (2012),” which led to one of the sections of Communicating in Spanish: The Best Option . This book is divided into several sections, and the section mentioned is titled “Share your ideas with your social network.” Methodology: An action research study was developed to achieve the aim. The method was inductive, as the use of a variety of readings and the writing of text messages allowed foreigners to use social networks for academic purposes. The exercises were applied to a group of four international students: three German students and one Chinese student between the ages of 18 and 23 interested in learning, improving, and speaking Spanish as a foreign language (ele). Results: It was found that the international students improved their literacy processes: this was reflected in the recognition and contextualization that the ele learners demonstrated when completing each reading and writing exercise through text messages and the communicative intentions surrounding their use in certain contexts. Conclusions: In adherence to the instructions of the exercises in the section titled “Share your ideas with your social network” in Communicating in Spanish: The Best Option , international students initially completed the exercises by using reading and writing on social networks. This research greatly contributed to the learners’ command of the Spanish language.